Suppliers selection and order allocation in the environment of supply chain based on fuzzy multi-objective integer programming model - Hong Huo; Zhuangpin Wei (2008 IEEE International Conference on Service Operations and Logistics, and Informatics, 2008)
Suppliers selection is one of the most critical activities of purchasing management in a supply chain, because of the key role of suppliersiquest performance in achieving the objectives of a supply chain. Suppliers selection is a multi-criteria decision-making (MCDM) problem which includes both tangible and intangible factors. In practice, vagueness and imprecision of the objectives, constraints and parameters in this problem make the decision-making complicated. In this paper, a weighted fuzzy multi-objective integer programming model, which represents decision makers' preference and objective fuzziness, is proposed to deal with the suppliers selection and order allocation problems in the supply chain system. Finally, a numerical example illustrates the method is simple and effective.